The Effectiveness of Using Fan-N-Pick Strategy Towards Students’ Vocabulary Mastery - Silvia, Ade; Zuhriyah, Mukminatus (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
The purpose of this study was to determine whether the Fan-N-Pick technique significantly affected the students' vocabulary mastery both before and after it was used. A pre-test-post-test with a single group was the design used in this pre-experimental research. Class IV students from a state primary school in Plandaan, Jombang, served as population in this study. There were twenty total students, of which eighteen were the sample. Before beginning the two-meeting treatments utilizing the Fan-N-Pick technique, the experimental students were given a pre-test of twenty multiple-choice questions. The post-test was completed using the same question from the pre-test after the treatment finished. After compiling all vocabulary test results, SPSS was used to apply the descriptive statistics, normality test, and paired sample t-test. The t-test result showed that Sig. (2-tailed) value is 0,000, which is lower than the alpha value of 0.05. That result revealed that the students’ vocabulary mastery significantly increased before and after the Fan-N-Pick strategy application. Thus, the Fan-N-Pick strategy was effective for teaching vocabulary. Then, it is highly recommended for English teachers to teach vocabulary using the fan-the-pick strategy.